Princess Mary's household and the succession crisis, July 1553 - Whitelock, A; MacCulloch, D (Cambridge University Press, 2007)
This article reconsiders Mary Tudor's victory in the succession crisis of July 1553. It challenges the traditional interpretation which accounts for Mary's unexpected triumph as the result of a 'spontaneous' rising of the East Anglian gentry. Instead it reclaims a central role for Mary's household affinity in the succession crisis and as such presents a longer-term perspective than accounts of Mary's coup d'état have provided hitherto. It concludes by pointing to the implications of the role of Mary's household for interpreting the politics and religion of her reign.